Pengembangan Media Belajar Interaktif berbasis kebudayaan lokal Kota Prabumulih untuk Anak-Anak Usia Dini berbasis Android - Wijaya, Khana; Ariansyah, Ariansyah; Samosir, Hepnyi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
As time passes, technological progress develops very rapidly and has a significant impact in various fields, one of which is education. Education is a learning process obtained by every human being, in this case, students; the aim is to make students understand, comprehend, and think more critically. Education can be formulated as guidance for human growth from birth until physical and spiritual maturity is achieved in the interaction of nature and the social environment. Education is a continuous process, it does not stop. Education is the most important thing in our lives because, with education, humans can be helped to survive and solve problems. And being an educated person is very important. The first education we get is from the family, school, and community environments. Early childhood is a golden age for children to accept and capture new things. The method used by researchers in this research is descriptive with a qualitative approach. This research aims to build an educational game application that young children can implement. The design and development of this application helps children aged 3-5 years to better understand material about recognizing letters, numbers, fruit, animal colors, shapes and vehicles. It also optimizes the function of Android devices owned by parents to serve as educational tools for their children